Incubação de ovos de codornas europeias sob diferentes temperaturas - João Vitor Santana Prates (2024)
Temperature is a factor that directly influences the yield and success of artificial incubation of eggs, an important stage for global poultry production, and it is necessary to establish an ideal temperature that intensifies the hatchability and quality of the animals, enhancing their future performance. For European quail there are no studies related to incubation temperatures, when compared to Japanese quails and chickens. The aim was to study and understand the use of different temperatures in incubating European quail eggs. 1000 eggs from two genetic groups were incubated at five different temperatures (37; 37.5; 38; 38.5 and 39 ± 0.2 ºC), with relative humidity at 60% and turning every two hours. At birth, incubation time, hatchability, embryodiagnosis, weight and morphological quality of the quails were evaluated. Of the animals born, 486 were distributed in breeding batteries to evaluate body weight, weight gain, feed consumption and feed conversion at 35 days. Temperatures demonstrated effects on all variables analyzed. A quadratic effect of temperatures was observed for hatchability, quail weight at birth and phase 3 of embryodiagnosis, and linear effect for phase 1 and for body weight, weight gain and feed consumption at 35 days. For incubation time, the average temperatures of 38.5 and 39 ºC did not differ from each other, as the averages for morphological quality at temperatures of 37 and 37.5 ºC; 37.5 and 39 ºC and 38; 38.5 and 39 ºC had statistically equal averages between them. In the quadratic effects, extreme temperatures presented lower results, while in the linear effect, lower results were observed at the lowest temperature, which increased as the temperature increased. In general, the incubation of European quail eggs can be carried out at an average temperature of 38.3 ºC, providing excellent results in terms of hatchability, hatch weight, quality and performance.